Exploring Multisystemic Resilience among Youth of Color Exposed to Direct and Indirect Violence - Jamison, Lacy E.; Howell, Kathryn H.; Campbell, Kaytryn D.; Thomsen, Kari N.; Hasselle, Amanda J. (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2023)
Objectives: Youth of color (YOC) are more likely to experience direct and indirect violence compared to non-Hispanic White youth. Although the negative consequences of violence exposure are well-established, less is understood about factors that may facilitate resilience.Methods: The current study utilized hierarchical linear regression modeling to examine the associations between resilience and psychological health, social support, and school engagement among YOC in the United States who have experienced violence. Participants included 75 YOC (Mage = 9.39; SD = 1.56; 84.1% Black or African American, 9.3% Biracial or Multiracial, 5.3% Hispanic, 1.3% Indigenous) who were directly or indirectly exposed to violence in the past year. They were recruited from a family justice center in the southern United States.Results: The final model was significant (F(5,74) = 21.71; p < .001) and accounted for 57% of the variance in resilience. Specifically, lower levels of direct violence exposure (β = -.18; p = .002), greater social support from friends and nonparental adults (β = .35; p < .001), and more school engagement (β = .47; p < .001) were related to higher resilience.Conclusions and Implications: Findings highlight the importance of interpersonal and school resources in facilitating resilience among YOC who have been exposed to violence. Clinicians are encouraged to connect YOC with accessible resources to foster behavioral, cognitive, and emotional involvement in school. Further, mental health care providers can assist YOC by helping them establish and maintain supportive relationships, which may enhance resilience.